2022
DOI: 10.3390/plants11050659
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Plant Growth Promoting Rhizosphere Microbiome as Alternative Biofertilizer in Boosting Solanum melongena L. Adaptation to Salinity Stress

Abstract: Recent ecological perturbations are presumed to be minimized by the application of biofertilizers as a safe alternative to chemical fertilizers. The current study aims to use bioinoculum (I) as an alternative biofertilizer and to alleviate salinity stress in the cultivar Solanum melongena L. Baldi. The salinity drench was 200 mM NaCl (S), which was used with different treatments (0; I; S; S + I) in pots prefilled with clay and sand (1:2). Results showed that salinity stress inhibited both plant fresh and dry w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 98 publications
0
2
0
Order By: Relevance
“…The P content increased with increasing salt concentration, although this increase was statistically different depending on the rice variety. Similarly, stress studies conducted on different plants have also recorded varying levels of increase and decrease in P content depending on the species and concentration (Bhattarai et al, 2022;Mokabel et al, 2022). In our study, as the salt concentration of NaCl and CaCl2 increased, the P content increased and was found to be higher than the control at 90 mM NaCl concentration.…”
Section: Mineral Element Contentssupporting
confidence: 69%
See 1 more Smart Citation
“…The P content increased with increasing salt concentration, although this increase was statistically different depending on the rice variety. Similarly, stress studies conducted on different plants have also recorded varying levels of increase and decrease in P content depending on the species and concentration (Bhattarai et al, 2022;Mokabel et al, 2022). In our study, as the salt concentration of NaCl and CaCl2 increased, the P content increased and was found to be higher than the control at 90 mM NaCl concentration.…”
Section: Mineral Element Contentssupporting
confidence: 69%
“…A decrease in Ca content was observed in rice varieties with varying levels of salt tolerance in response to salt stress, while the change in K content in the leaves of the treated plants was not statistically significant (Thu et al, 2017). Mokabel et al (2022) reported that using the microbiome to alleviate the effects of salt stress in Solanum melongena (eggplant) resulted in a significant reduction in Ca and K levels compared to the control group. In addition, they observed a decrease in Mg content in plants treated with 200 mM NaCl, but this decrease was not statistically significant.…”
Section: Mineral Element Contentsmentioning
confidence: 99%
“…Considerable research efforts have been directed toward using specific microorganisms, mainly plant growth-promoting rhizobacteria (PGPR), within agriculture. These PGPR serve as biofertilizers or biostimulants, contributing to improved soil fertility, enhanced plant growth, increased yield, and, ultimately, a better use of chemical fertilizer under diverse environmental conditions (Raklami et al 2019 , Anli et al 2020 , Mokabel et al 2022 , Sedri et al 2022 ). Yeasts have received less attention among microbial species due to their relatively low population density.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic fertilizers are widely used globally to increase the productivity of numerous crops [3]. Nonetheless, using chemical fertilizers above the threshold levels results in environmental pollution, land degradation, and high soil acidification [4]. In terms of the production of many commercial crops, the adverse effects of long-term usage of synthetic fertilizers, such as weed infestation [5], opportunistic diseases [6], and pests [7], have been reported in relation to how they cause crop yields to decline.…”
Section: Introductionmentioning
confidence: 99%